The Control of skincare and bodycare inventory decisions using the Multi Attribute UtilityTheory (MAUT) Method - Sinaga, Ismi Novitasari (Jurnal Mandiri IT, 2024)
Skincare is a series of facial skin care activities to maintain the health and appearance of the skin, as well as overcome various problems with skin. This activity consists of using several types of products, each of which has a different function according to its contents. In companies operating in the supply and trading sector, it is one of the core variables of business operations. Inventory management is also very important in company operations. Inventory that is not managed properly will cause many operational problems, such as running out of products or raw materials when needed, losing customers, losing goods, and other aspects of loss that can have a significant impact on the company.  For this reason, this research aims to make decisions on controlling skincare supplies so that they can be guaranteed in sufficient quantities with decision support using the MAUT method. The data used in this research is the number of supplies that run out per day, per week, per month. It is hoped that the results of this research with the Multi Attribute Utility Theory (MAUT) method can help companies in making decisions on controlling skincare supplies very well.